2013
DOI: 10.1159/000355717
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Clinical Significance and Related Factors of Thirst and Xerostomia in Maintenance Hemodialysis Patients

Abstract: Aims: To analyse the clinical significance and related factors of thirst and xerostomia and to find methods to alleviate thirst and xerostomia in maintenance hemodialysis (MHD) patients. Methods: Forty-two MHD patients were included for observational study and eleven patients were enrolled for crossover trial. Thirst was assessed by 100-mm visual analog scales (VAS) and dialysis thirst inventory (DTI). Meanwhile, xerostomia was assessed by VAS and xerostomia inventory (XI). Depression, kidney disease quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
110
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(121 citation statements)
references
References 38 publications
7
110
0
2
Order By: Relevance
“…Likewise, some studies have observed the existence of a positive correlation among thirst, xerostomia and IDWG in HD patients (11,14,18,19). These factors could contribute on morbidity and mortality of HD patients.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Likewise, some studies have observed the existence of a positive correlation among thirst, xerostomia and IDWG in HD patients (11,14,18,19). These factors could contribute on morbidity and mortality of HD patients.…”
Section: Introductionmentioning
confidence: 85%
“…HD patients have to maintain a correct fluid volume balance, which should be achieved by daily restrictions in fluid consumption. Improper drinking behaviours in HD patients lead to fluid overload, which may give rise to hypertension, pulmonary oedema or other cardiovascular manifestations (11,18). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is conceivable that patients who consume more protein have a higher salt intake resulting in thirst. Thirst is prevalent in dialysis patients and is associated with higher IDWG and lower quality of life [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients on HD may be particularly vulnerable to such triggers because of thirst augmentation from wide serum-dialysate sodium gradients (21). In fact, increased thirst among patients on HD is associated with increased IDWG and reduced quality of life (22).…”
Section: Discussionmentioning
confidence: 99%